Isolated intestinal ganglioneuromatosis - A rare entity - Laudari, Uttam; Rupakheti, Shail; Bohara, Tanka Prasad; Joshi, Mukunda Raj; Lakhey, Mamta (Journal of Kathmandu Medical College, 2017)
Intestinal ganglioneuromatosis are rare benign tumour of ganglionic cell origin, most of them associated with neurofi bromatosis type I and multiple endocrine neoplasia type IIB. They are benign tumours with rare malignant transformation, have a varied clinical presentation and long indolent course. Surgical resection is the only modality of treatment and diagnosis is based on histopathological examination and immunohistochemistry. We report a case, 55 year old male who was diagnosed as a case of isolated intestinal ganglioneuromatosis, i.e no association with neurofibromatosis type I and multiple endocrine neoplasia type IIB. He is on regular follow up with normal daily activities and no evidence of recurrence.Journal of Kathmandu Medical College, Vol. 5, No. 4, Issue 18, Oct.-Dec., 2016, Page: 131-135